2022
DOI: 10.1097/pxr.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

The preliminary results of physiotherapy scoliosis-specific exercises on spine joint position sense in adolescent idiopathic scoliosis: A randomized controlled trial

Abstract: Background:It has been observed that there are difficulties in maintaining spinal harmony in the absence of proprioceptive information, which has an important role in achieving postural control in scoliosis. One of the tests used to evaluate proprioceptive mechanisms is joint position reproduction.Objective(s):The main aim of our study was to investigate the effect of physiotherapy scoliosis-specific exercise (PSSE) on spine joint reposition (JR) sense. The second aim was to determine the effects of PSSE on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Cobb angle and ATR angle are important predictive factors for good prognosis in AIS patients. 20 The results of this study showed that the total efficacy of the experimental group was higher than that of the control group at six and 12 months after treatment. It shows that the combination of laser acupuncture therapy and Schroth therapy can quickly correct scoliosis, significantly enhance the clinical effect, and make AIS patients recover quickly.…”
Section: Discussionmentioning
confidence: 62%
“…Cobb angle and ATR angle are important predictive factors for good prognosis in AIS patients. 20 The results of this study showed that the total efficacy of the experimental group was higher than that of the control group at six and 12 months after treatment. It shows that the combination of laser acupuncture therapy and Schroth therapy can quickly correct scoliosis, significantly enhance the clinical effect, and make AIS patients recover quickly.…”
Section: Discussionmentioning
confidence: 62%
“…The assessment of swimmers' posture through the use of a mobile application represents a pioneering and practical approach that can accurately detect deviations from optimal posture using objective data. PostureScreen, an evidence-based software for postural analysis, is applicable in both clinical settings [40] and sports research [25,33,41] . In our study, the implementation of PostureScreen proved to be a reliable method for objectively identifying alterations in body posture and monitoring changes in young swimmers' postural alignment.…”
Section: Discussionmentioning
confidence: 99%